Yeast enhancement by mass mating and selective pressure for the integrated production process of first and second-generation ethanol - Muynarsk, Elisangela de Souza Miranda [UNESP]; Christofoleti-Furlan, Renata Maria; Colonia, Brigitte Sthepani Orozco; Júnior, Edis Belini; da Silva, Danilo Grünig Humberto [UNESP]; Basso, Luiz Carlos (Zeppelini Editorial e Comunicacao, 2024)
Second-generation ethanol production is a worldwide applicable technology with the potential to replace fossil fuels and contribute to sustainability. The incorporation of second-generation ethanol production in Brazilian biorefineries, besides the technological advantages, adds to the abundance of feedstock derived from the sugar and alcohol industry itself. However, developing yeast strains that resist the inhibitory conditions of the new substrate, potentiated by cellular recycling, is extremely necessary. The aim of the present work was to develop yeast strains by hybridization and selective pressure techniques, with multi-tolerant profile for the fed-batch fermentation process using a mixture of molasses and bagasse hydrolysate as substrate. Therefore, the mass crossing technique was carried out involving five strains of Saccharomyces cerevisiae, previously selected, for demonstrating high tolerance to fermentation from mixed-must composed of lignocellulosic hydrolysate and sugarcane molasses. The culture resulting from the mass mating was followed by a selective pressure during 51 generations, generating enrichment of more tolerant strains. Employing microplate growth evaluation (optical density [DO] 600 nm), ten evolved isolates were selected, which were submitted to lab scale fermentation, simulating industrial conditions to the maximum. In the end, it was possible to highlight a lineage (C8E1-13T) presenting trehalose reserve content significantly higher than the other lineages evaluated, thus demonstrating the generation of an improved phenotype.
Aprimoramento de leveduras por cruzamento massal e pressão seletiva para o processo integrado de produção de etanol de primeira e segunda gerações
Keywords: biofuel; hybridization; inhibitors; lignocellulosic hydrolysate; tolerance